Effect of rocks displacement activation on the formation of the surface trough during anthracite seams extraction - Filatiev, M. (Розробка родовищ, 2017)
Purpose. To define peculiarities related to the formation of the dynamic and stationary half-troughs under the influence of anthracite seam extraction by adjacent faces. Findings. The effect of rocks displacement activation on the formation of the dynamic half-trough on the surface is established.